Law and democracy : contemporary questions - Patmore, G. A. (Glenn Anthony), 1961-; Rubenstein, Kim (Australian National University Press, 2014)
Law and Democracy: Contemporary Questions provides a fresh understanding of law's regulation of Australian democracy. The book enriches public law scholarship, deepening and challenging the current conceptions of law's regulation of popular participation and legal representation.
Keywords: Democracy -- Australia.; Constitutional law -- Australia.; State, The.; Political science -- Australia.; Australia -- Politics and government.; Jurisprudence & general issues.; POLITICAL SCIENCE -- Political Ideologies -- Democracy.; Politics and government; Constitutional law.; Democracy.; Political science.; Australia.; law.; australia.; politics.; democracy.; Electronic books.; Conference papers and proceedings.